At a Crossroads: Economic Hierarchy and Hardship at the Intersection of Race, Sex, and Nativity. (December 2019) - Restifo, Salvatore J.; Mykyta, Laryssa
Immigration has been the focus of much contention in the United States in recent years. Indeed, concerns persist with regard to how the foreign-born will adapt and integrate into U.S. society and core institutions, including the economy and labor market. Despite the considerable insights of prior research, however, our understanding of contemporary racial/ethnic stratification remains limited, especially in terms of how race/ethnicity and sex intersect with immigrant status. Using pooled 2012–2016 American Community Survey data, we investigate wage differences and near-poverty status by race/ethnicity, sex, and nativity (among full-time, full-year workers) in five dynamic majority-minority U.S. labor markets and high-volume immigrant destinations (Atlanta, Chicago, Houston, Los Angeles, and New York City). Findings demonstrate that assimilative and human capital attributes matter. Yet our analyses reveal discernible group-level inequalities suggestive of depressed mobility, blocked opportunity, and race/ethnic- and sex-based hierarchy—patterns that highlight the embedded character of assimilation and economic outcomes within contexts of constraint. We find significant inter- and intragroup variation in these regards—particularly for near-poverty. We discuss our findings in light of their empirical and theoretical implications toward understanding minority group incorporation and economic inequality.